Presence and distribution of the brown bear (Ursus arctos) in Friuli Venezia Giulia, from 2004 to 2011, through the non-invasive genetic monitoring ad conservation implications - Caboni, A; Giangregorio, P; Davoli, F; Randi, E; Fattori, U; Visintin, A; Filacorda S.; LO BIANCO, Stefania (2012)
After having disappeared at the beginning of 1900, the brown bear has started in a late 1960s a slow process of recolonization of the north-eastern Alps, through an expansion of Dinaric population. At the end of the 1990s the University of Udine began the occasional monitoring of the species and from 2004 non-invasive genetic monitoring became systematic. In the last 8 years 217 hair traps have been activated in the region to monitore: Natisone Valleys, the Julian and Carnic Alps and Prealps. Twenty-six hair traps were monitored in all years, whereas 40 were observed only in 2004, 2007 and 2011. The 26 hair traps constantly monitored from 2004 to 2011 showed 17% of average success of hair’s collecting (brown bear samples collected/day control: BBSD). The 40 hair traps, monitored in the window period, showed 12% of BBSD. The BBSD value varied in relation to both season (highest in spring) and year, with a dramatic decline from 2008, and interaction between year and area. From 2004, 13 genotypes, through systematic hair traps monitoring, were identified, while only 2 genotypes were sampled opportunistically. It was observed a high turnover of the genotypes: only 7 genotypes were sampled for more than 2 years (47% of total), 4 genotypes (27% of the total) were sampled for 3 years or more. The annual attendance of bear have been constant from 2004 to 2007, with 5-6 genotypes present every year. In the period between 2008 and 2010 there was a drastic decrease in the successful collection at the hair traps, with and average of 1-2 animals genotyped per year. However, opportunistic samples have increased in the recent times, probably due to the arrivals of 3 genotypes from Trentino (KJ2G2 in 2009 and DG2 and MJ4 in 2011). The year 2011 showed a further increase in the presence of bears with 5 animals genotyped in Friuli Venezia Giulia. Three of these animals belonged to the Slovenian population, while the other 2 genotypes were from the Trentino population. The results seem to confirm the exchange of some individuals ...